Математичне моделювання зв’язку об’єму і висоти сипкого матеріалу у промислових ємкостях - Мацуй, Анатолій Миколайович; Кондратець, Василь Олександрович (НТУ "ХПІ", 2017)
Запропоновано моделі конічного бункера для сипких продуктів, які зв’язують відносні похибки висоти матеріалу і його неврахованого об’єму. При неврахованих об’ємах матеріалу до 12 … 15 % вихідного значення абсолютні і відносні відхилення його висоти також змінюються. Отримані моделюванням відношення відносних похибок визначення висоти матеріалу і об’єму складає 1/3 і не залежать від висоти матеріалу і параметрів бункера.

Basic and alternative models of conical hopper for pouring or liquid products, which connect the relative height error of the material and its unaccounted volume in the form of algebraic equations of the third degree, are proposed. The numerical solutions of the equations show that the ratio of the relative deviations of the material height and volume is a constant value for comparatively small volumes of unaccounted material in the hopper, which do not exceed 15 % of the total value. A wider range of deviations of the unaccounted volume in the interval of 20 ... 50 % of the initial value do not violate the established trend of changing the ratio of the relative height deviations of the material to its volume. The ratio of the relative errors of determining the height of the material to relative error of measuring its volume obtained during modeling is 1/3 and does not depend on the height of the material and the hopper parameters.
Mathematical modeling of relation of volume and height of pouring materials in industrial capacities
Keywords: конічний бункер; відносні похибки; рівнеміри; вимірювання запасу матеріалу; conical hopper; pouring material; relative errors; height; volume